2019
DOI: 10.18203/2319-2003.ijbcp20195271
|View full text |Cite
|
Sign up to set email alerts
|

A 12 week prospective clinical evidence of empagliflozin efficacy in uncontrolled type 2 diabetes mellitus treated with metformin and a sulfonylurea

Abstract: Background: The main aim of the study is to evaluate the efficacy of empagliflozin 10 mg once daily over 12 weeks as add-on therapy to metformin plus sulfonylurea in patients with type 2 diabetes mellitus with inadequate glycemic control.Methods: It is a prospective, observational, study conducted in patients of Sri Badhrakali Diabetic Center located in Warangal, Telangana, India. The efficacy of empagliflozin 10 mg was assessed by measuring the change in the glycated hemoglobin (HbA1c), fasting plasma glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Our study found that the mean systolic and diastolic blood pressures decreased from 129 mmHg to below 120 mmHg (p < 0.001) and 82.3 mmHg to below 80 mmHg (p = 0.029), respectively, after three months of intervention. Our findings were in good agreement with Puli and Vanjari & Zhong et al 13,15 Puli and Vanjari, 13 in a prospective study demonstrated that at 24 hours, empagliflozin significantly reduced blood pressure with mean change in SBP and DBP were 4.147 and 1.526 mmHg respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found that the mean systolic and diastolic blood pressures decreased from 129 mmHg to below 120 mmHg (p < 0.001) and 82.3 mmHg to below 80 mmHg (p = 0.029), respectively, after three months of intervention. Our findings were in good agreement with Puli and Vanjari & Zhong et al 13,15 Puli and Vanjari, 13 in a prospective study demonstrated that at 24 hours, empagliflozin significantly reduced blood pressure with mean change in SBP and DBP were 4.147 and 1.526 mmHg respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The overall reduction of FBS from baseline to 12 weeks of intervention is statistically significant (p < 0.001), which was in line with the study of Puli and Vanjari and Søfteland and associates. 13,14 Puli and Vanjari, 13 in a prospective study in India, demonstrated that the mean change of FBS from baseline to 12 weeks was 26 mg/dl. Søfteland and associates 14 evaluated the efficacy and safety of empagliflozin as add-on therapy in inadequately controlled type 2 diabetic patients under treatment of linagliptin and metformin and found that fasting blood sugar (FBS) and weight was significantly reduced in both empagliflozin groups versus placebo (p<0.001 for all comparisons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation